(untitled) (Journal of history, 2017)
The article is devoted to ethnographic peculiarities of spring festival of Turkic-Muslim world - Novruz. In Azerbaijan, the preparation for the celebration of Nowruz begins well, more precisely, a month before the arrival of the ego. And within a month before the holiday the night from Tuesday to Wednesday of each week is a holiday. A feature of the four nights that they are devoted to the worship of the four elements: water, fire, air and earth.The first Tuesday, called Water Tuesday, is also known in various regions of Azerbaijan as First Tuesday, Novruz of Waters, Small Tuesday, False Tuesday and Dust Tuesday. Each of these has its own meaning and rituals. It is called First Tuesday because it is the first of the Right Tuesdays and False because summer is still a long way off and can’t yet be felt. Dust Tuesday refers to the fact that people would clean their houses, clothes and carpets of dust, whilst Small Tuesday reflects that this Tuesday isn’t celebrated as much as the others.On this Tuesday, a bonfire is constructed in yards and squares and people jump over it to cleanse themselves of all the pain, hardship and distress of the last year.